Otimização do protocolo de vitrificação e estabelecimento do sistema de cultivo in vitro para o tecido ovariano de cutias (dasyprocta leporina) - Praxedes, Érica Camila Gurgel (Universidade Federal Rural do Semi-Árido, 2021)
The agouti are wild mammals that have important ecological functions for being seed dispersers, in addition to contributing to the balance of the food chain. These animals are used as an experimental model both for the improvement of reproductive techniques and for the formation of germplasm banks. In this context, the aim of the present study was to use the manipulation of oocytes included in preantral ovarian follicles (MOIFOPA) as a tool for the rescue and conservation of the use of female agouti gametes (Dasyprocta leporina). The thesis was divided into two experimental chapters. In the first experiment, the use of TCM-199 supplemented with different concentrations of pFSH (10 and 50 ng/mL) was analyzed on the morphology, development and viability of preantral ovarian follicles (PAFs) included in ovarian tissue. Then, the effect of this in vitro culture system (IVC) on the same PAFs parameters prior to vitrification was verified. After cultivation, the FSH50 group had a higher percentage of morphologically normal follicles when compared to the FSH10 group (P < 0.05). Furthermore, this same response was observed for primordial follicles. Regardless of the FSH concentrations used during the IVC, no difference was observed in relation to the percentage of viable follicles (P > 0.05). Thus, the FSH50 group was used for a further experiment, in which a total of 76.2 ± 7.2% of previously vitrified normal PAFs was observed after 6 days of cultivation, with the highest values (P < 0.05) for the morphology of the primordial follicles (95.2 ± 4.7%). However, the culture maintained the viability of FOPAS derived from cryopreserved tissues (P > 0.05). In the second experiment, the ovaries of eight females were retrieved and fragmented, with four cortex fragments immediately fixed and evaluated (fresh group). The remaining fragments were processed by the solid surface vitrification (SSV) or ovarian tissue cryosystem (OTC) method using fetal bovine serum (SFB), ethylene glycol (EG) and sucrose (SAC) as cryoprotectants, stored for two weeks at -196 ºC and heated. Afterwards, the fragments were submitted to an in vitro culture for 24 h and evaluated for microbiological load, PAFs morphology and DNA integrity. There was no fungal contamination; however, vitrified samples from two individuals showed bacterial contamination of 79,200 colony-forming units per milliliter (CFU) / mL for SSV and 3.120 CFU / mL for OTC. Regarding the morphology of PAFs, both systems provided adequate preservation of morphology, with values above 70% of normal follicles observed before and after cultivation. TUNEL revealed that both SSV (52.39%) and OTC (41.67%) can preserve DNA integrity after vitrification and after 24 h of culture. For cell proliferation, low rates were detected for fresh samples (11.53%) and SSV (29.87%); however, no evidence of proliferation was found when OTC was used. Thus, the use of manipulation of oocytes included in preantral ovarian follicles in agouti allowed conservation through vitrification on solid surface and using the OTC system, as well as presented promising results for the in vitro culture of PAFs included in previously vitrified ovarian tissue
Keywords: Folículos; Germoplasma; Cultivo in vitro; Cutia; CIENCIAS AGRARIAS::MEDICINA VETERINARIA